Mathematical Simulation of the Heat and Mass Transfer in the Movement of Liquid Droplets in a Gas Medium Under the Conditions of their Intense Phase Transformations; Journal of Engineering Physics and Thermophysics; Vol. 93, iss. 5 - Antonov D. V. Dmitry Vladimirovich (2020, 2020)
Title screen